AQSĀM AL-QUR`AN: GAYA BAHASA AL-QUR'AN DALAM PENYAMPAIAN PESAN - Misnawati Misnawati (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2020)
Qasam is one of the Arabs' habit since pre-Islamic in communicating to convince the interlocutor (mukhathab). This habit continues until Islam comes with the Qur'an as a guide to human life. The Qur'an descended on their environment and adapted to their habits in delivering divine messages. Human psychological conditions on receiving the message of Allah I are different. Some receive the message without the slightest doubt in their minds, so there is no need to swear to convince him and those who feel doubtful about the divine message so it is necessary to the amplifier and ironically, there is no confidence in the divine kalam, so that it must be accompanied by more than one amplifier. In the swearing, several elements must be fulfilled, namely fi`il qasam, muqsam bih, and muqsam alaihi. There are two models of qasam in the Qur'an, qasam zhāhir; which is clearly visible  fi`il qasam and muqsam bih, while qasam mudhmar; the fi`il qasam and muqsam bih are not mentioned. The existence of qasam in the Koran to eliminate doubts and misunderstanding mukhāthab of the al-Qur'an itself, which is why they increase their confidence in it and the truth is established that the Koran is truly a revelation of Allah I and revealed to the Prophet Muhammad r to be transmitted to the humankind.